FORGIVENESS PADA PRIA DAN WANITA DEWASA AWAL YANG MENGALAMI FATHERLESS DI KOTA TOMOHON - Bago, Anggun; Lumapow, Harol; Hartati, Meike (PSIKOPEDIA, 2024)
This research aims to determine the description of forgiveness in early adult men and women who experience fatherlessness in Tomohon City. This research uses a qualitative research method with a case study approach. The technique used in data collection is interviews. The research results obtained show that forgiveness in early adult men and women is different. In the early adult male subject, he has forgiven, where there is no more avoidance, does not harbor negative emotions, and is willing to be kind to his father and try to maintain a good relationship. Factors that influence this include the closeness of the child and his father, as well as religiosity which makes the subject able to forgive. Meanwhile, in early adult women, the subject has not fully forgiven where the subject does not want to meet and communicate with his father, there are still feelings of anger and disappointment towards his father, but the subject is willing to help his father when he is in trouble but is not ready to have a closer relationship with his father.